Geriatric Nutritional Risk Index as a Prognostic Marker for Patients With Metastatic Castration-Resistant Prostate Cancer Receiving Docetaxel - Chang, Li-Wen; Hung, Sheng-Chun; Li, Jian-Ri; Chiu, Kun-Yuan; Yang, Cheng-Kuang; Chen, Chuan-Shu; Lu, Kevin; Chen, Cheng-Che; Wang, Shu-Chi; Lin, Chia-Yen; Cheng, Chen-Li; Ou, Yen-Chuan; et al. (Frontiers in Pharmacology, 2021)
Purpose: To investigate the prognostic efficacy of the Geriatric Nutritional Risk Index (GNRI) in patients with metastatic Castration–resistant Prostate Cancer (mCRPC) receiving docetaxel as the first line of treatment. Methods: We retrospectively reviewed patients with mCRPC and receiving first line docetaxel in Taichung Veterans General Hospital from 2006 to 2012. The GNRI was calculated using serum albumin and body mass index, with a poor nutritional status defined as GNRI <92.0. Multivariate Cox-regression analysis was used to evaluate the risk of survival. Results: One-hundred seventy patients with mCRPC were included. One-hundred twenty-five patients were of normal nutritional status (GNRI ≥92) and 45 patients were of poor nutritional status (GNRI <92). The cumulative docetaxel dosage was 600 (360–1,185) mg in the normal nutritional status group and 360 (127.5–660) mg in the poor nutritional status group (p < 0.001). The median overall survival from mCRPC was 30.39 months in the good nutritional status group and 11.07 months in the poor nutritional status group (p of log rank <0.001). In a multivariate model, poor nutritional status was an independent risk factor in overall survival (Hazard Ratio [HR] = 5.37, 95% Confidence Interval [CI] 3.27–8.83), together with a high metastatic volume (HR = 4.03, 95% CI 2.16–7.53) and docetaxel cumulative dosage (HR = 0.999, 95% CI 0.999–0.9998). Conclusion: Poor nutritional status with a GNRI <92 is associated with shorter progression free survival and overall survival in mCRPC patients treated with docetaxel. Metastatic volume and cumulative docetaxel dosage are also independent prognostic factors in overall survival.